Ensinar a alunos com deficiência visual: conflitos e desenvolvimento - Silva, Rosycléa Dantas (2014)
Inclusive education is still gaining forms and meanings, so it has been seen as a space for debates and pieces of research, among them which those related to the difficulties of foreign language teaching for students with visual impairment. Therefore, grounded in Applied Linguistics, this paper tries to understand the English teacher‟s work to students with visual impairment taking into account the Sociodiscursive Interactionism theoretical framework (BRONCKART, 1999, 2006, 2008), bearing in mind that it allows investigating teachers work through their own speech. It also uses legal documents (decrees, laws, ordinances, curriculum guidelines) that govern inclusive education, studies about people with visual impairment (VYGOTSKY, 1993 [1934]; SACKS, 2010), pieces of research on FL teaching for these people (Motta, 2004 MEDRADO and DANTAS, 2011) and, moreover, assumptions about the relationship between conflict and development (VYGOTSKY, 2000; CLOT, 2007). This project aims at investigating how English teachers, in teaching activity to students with visual impairment, see themselves as their teachers. Thus, it started from the hypothesis that the meanings which teachers attach to their practice to students with visual impairment show a confrontational teaching activity and also a lack of training, and it was considered the analysis of voices and thematic contents present in teachers‟ speech. The methodological apparatus of Sociodiscursive Interactionism was used to collect the corpus doing interviews and simple self-confrontations, which were carried out with four teachers from regular schools. The analysis evidenced the mobilization of four thematic contents by teachers, among which the lack of training for working with students with visual impairment and the reconfiguration of teaching activity from the conflict. The voices related to these thematic contents showed the strength of the collective as being crucial in the struggle for training courses and in the solution of problems, as well as the responsibility of teachers, represented by the empirical author's voice, in practice changes that could meet student‟s needs. From these themes and voices, teachers assign meanings to their practice, such as: a work permeated by conflicts.